Riwayat Paparan Pestisida dan Kadar Insulin Like Growth Factor I (Igf-1) pada Siswa SD Negeri Dukuhlo 01 Kecamatan Bulakamba Kabupaten Brebes - Hidayah, Nurul (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2016)
ABSTRACT Background: One of the areas in the Brebes Regency which as the largest usage of pesticides is the Dukuhlo Village Bulakamba Subdistrict Brebes Regency, because the extent of agricultural land, especially the on shallot. Children living in agricultural regions is one of the populations at risk for experiencing exposure to pesticides with adverse impact in the long term. The objective of this research was of history pesticide exposure with levels of serum Insulin Like Growth Factor I (IGF-1) on students of of public primary school Dukuhlo 01 Bulakamba Subdistrict Brebes Regency. Methods: This research was a cross sectional design, with 48 children. Data obtained from the results of the examination of the levels of Insulin Like Growth Factor I (IGF-1). Results: Results of the study showed that 15 (3.3%) of 48 children positive urine metabolit, and 18 of 48 children which examined the levels of IGF-1 have low (37.5%). The results showed no difference of IGF-1 mean on positive pesticide metabolit in the urine on child with IGF-1 mean on negative pesticide metabolit in the urine on child. Conclusions: The conclusions of this research are proportion on children positive urine metabolit and have a less IGF-1 more high (40%) than proportion on children negative urine metabolit and have a normal IGF-1 of public primary school Dukuhlo 01 Bulakamba Subdistrict Brebes Regency.